Identification of a Catalase-Phenol Oxidase in Betalain Biosynthesis in Red Amaranth (Amaranthus cruentus) - Teng, Xiao-Lu; Chen, Ning; Xiao, Xing-Guo (Frontiers in Plant Science, 2016)
Betalains are a group of nitrogen-containing pigments that color plants in most families of Caryophyllales. Their biosynthesis has long been proposed to begin with hydroxylation of L-tyrosine to L-DOPA through monophenolase activity of tyrosinase, but biochemical evidence in vivo remains lacking. Here we report that a Group 4 catalase, catalase-phenol oxidase (named as AcCATPO), was identified, purified and characterized from leaves of Amaranthus cruentus, a betalain plant. The purified enzyme appeared to be a homotrimeric protein composed of subunits of about 58 kDa, and demonstrated not only the catalase activity toward H2O2, but also the monophenolase activity toward L-tyrosine and diphenolase activity toward L-DOPA. Its catalase and phenol oxidase activities were inhibited by common classic catalase and tyrosinase inhibitors, respectively. All its peptide fragments identified by nano-LC-MS/MS were targeted to catalases, and matched with a cDNA-encoded polypeptide which contains both classic catalase and phenol oxidase active sites. These sites were also present in catalases of non-betalain plants analyzed. AcCATPO transcript abundance was positively correlated with the ratio of betaxanthin to betacyanin in both green and red leaf sectors of A. tricolor. These data shows that the fourth group catalase, catalase-phenol oxidase, is present in plant, and might be involved in betaxanthin biosynthesis.